EFFECT OF LCC AND SPAD BASED NITROGEN MANAGEMENT ON GROWTH AND YIELD OF LOWLAND RICE (ORYZA SATIVA L.) - DUTTARGANVI, SHANTAPPA; A. S. CHANNABASAVANNA,; RAO, SATYANARAYAN; A. S. HALEPYATI, (The Bioscan, 2014)
A field experiment was conducted at Raichur during kharif-2009 to validate the effect of Leaf Colour Chart (LCC) and Soil and Plant Analysis Development meter (SPAD) based nitrogen (N) management on growth and yield of lowland rice (Oryza sativa L.). Treatments consists of N application based on LCC thresholds (3.5 to 5.0) and SPAD values (30 to 40) compared with state recommendation and farmers’ practice (220 kg ha-1), were imposed through RCBD replicating thrice. The results revealed that N application based on LCC values @ 5 (120 kg ha-1) and SPAD @ 37.5 (120 kg ha-1) were more beneficial in enhancing the growth and yield of the low land rice. The split application of N at higher doses enhances its uptake over basal application. Significantly better growth parameters were recorded when N requirement for rice was applied based on LCC @ 5 (120 kg ha-1)) and SPAD @ 37.5 (120 kg ha-1). These were also recorded better yield parameters over farmers’ method and low N rates treatments. The results of the study implied that LCC threshold @ 5.0 or SPAD @ 37.5 are found to be effective as a decision tool for optimum N application in rice.